Viscose filament Hadamard fabric desizing-free sizing agent, sizing agent and desizing-free sizing weaving process
By using desorption-free slurry made of oxidized acetate starch and PVA-0588, the sizing problem of low-fine viscose filaments in Hada weaving is solved, efficient weaving and environmentally friendly processes are achieved, and the mechanical properties and wrinkle resistance of the fabric are improved.
Patent Information
- Application Number
- CN202510126104.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-27
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-27
AI Technical Summary
The prior art is difficult to effectively solve the sizing problem of viscose filaments with low fineness in Hada weaving, resulting in poor weaving effect and environmental pollution.
The viscose filament Hada fabric desizing slurry is made of oxidized acetate starch and PVA-0588. Through a specific slurry preparation and sizing process, the efficient sizing and weaving of viscose filaments is achieved.
The performance of the yarn, such as strength, wear resistance, etc., makes the desorption-free fabric better than traditional sizing fabrics in terms of mechanical properties and wrinkle resistance, and saves energy and reduces the emission of desorption wastewater, which is in line with the development trend of green sizing.
Smart Images

Figure CN119859919A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of desizing-free weaving, in particular to a desizing-free sizing material, sizing liquid and a desizing-free sized yarn weaving process for viscose filament Hada fabric. Background Art
[0002] As one of the characteristic products of Tibet, Hada is consumed in huge quantities every year. At present, most Hada on the market are polyester or polyester-cotton blended products, which are cheap but difficult to biodegrade, causing serious damage to the fragile ecological environment of Tibet. Therefore, it is imperative to develop biodegradable Hada products.
[0003] Viscose fiber, as a type of cellulose fiber, can be completely degraded after being discarded, and is suitable for the development of fully biodegradable Hada products. However, it is difficult to weave directly on the machine. The viscose filaments need to be sized first to improve the wear resistance of the warp yarns before weaving on the machine. At present, the three major mainstream sizing agents on the market are starch sizing agents, polyvinyl alcohol (PVA) and polyacrylic acid sizing agents; the development of polyacrylic acid sizing agents is limited due to their high cost and problems such as moisture absorption and re-stickiness; while PVA has good compatibility with starch and excellent sizing performance, and cannot be completely replaced at present.
[0004] At present, there are many studies on new sizing processes, such as low sizing rate sizing. If the sizing rate is high, it will lead to hard and brittle sizing yarn, poor sizing effect, excessive sizing liquid consumption and other problems, which will affect subsequent weaving; medium and low temperature sizing not only saves a lot of energy but also provides a more comfortable working environment for operators; the desizing-free process refers to the warp yarn being sized and woven into fabric without traditional desizing treatment, and can directly proceed to subsequent processes. The desizing-free process avoids the generation of desizing wastewater and saves energy.
[0005] Therefore, developing a desizing-free sizing process for viscose filaments with lower fineness suitable for Hada weaving is of great significance to Hada weaving and environmental protection. Summary of the invention
[0006] The purpose of the present invention is to provide a desizing-free sizing material and corresponding slurry for viscose filament Hada fabrics which can solve the above-mentioned technical problems.
[0007] Another object of the present invention is to provide a desizing-free yarn weaving process using the above-mentioned viscose filament Hada fabric desizing-free sizing material.
[0008] Another object of the present invention is to provide a Hada fabric woven by using the above-mentioned viscose filament Hada fabric desizing-free sizing material and the desizing-free yarn weaving process of the viscose filament Hada fabric desizing-free sizing material.
[0009] To this end, the technical solution of the present invention is as follows:
[0010] A desizing-free sizing material for viscose filament Hada fabric is compounded by oxidized acetate starch and PVA-0588, wherein the weight ratio of the two is (15-17):4, more preferably 4:1.
[0011] Preferably, the oxidized acetate starch is prepared from corn starch and cassava starch as raw materials through esterification and oxidation double modification; wherein the corn starch and cassava starch are a mixture in any proportion.
[0012] A slurry prepared from the desizing-free slurry of the viscose filament Hada fabric is prepared by adding water to the slurry to make the solid content of the slurry 2wt.% to 5wt.%; then stirring at 95℃ to 100℃ for 30min to 40min; finally keeping warm at 60℃ to 65℃ for 30min to 40min.
[0013] The slurry prepared by the desizing-free slurry of the viscose filament Hada fabric has a better sizing effect as the solid content increases, but the fabric will also be harder; according to experimental tests, when the solid content of the slurry is controlled in the range of 2wt.% to 5wt.%, the sizing effect is not much different, so it can be adjusted according to the fineness of the viscose filament.
[0014] A desizing-free sizing process for viscose filament Hada fabric using the above-mentioned sizing liquid comprises the following steps:
[0015] S1. Prepare slurry;
[0016] S2. Sizing the viscose filaments: the sizing temperature is set to 55°C to 60°C, the drying room temperature is set to 55°C to 60°C, the sizing speed is 20m / min to 25m / min, and the pressure of the sizing roller is 0.2MPa to 0.3MPa to obtain sizing yarn;
[0017] S3, weaving the sizing yarn into Hada fabric: the warp density is set to 300 (10cm) -1 ~420 pieces (10cm) -1 , the weft density is set to 200 (10cm) -1 ~300 pieces (10cm) -1 .
[0018] Preferably, in step S1, the oil agent is a mixture of castor oil and castor oil polyoxyethylene ether in a weight ratio of 1:1.
[0019] Preferably, in step S2, the viscose filaments are 11 tex to 15 tex viscose filaments.
[0020] Preferably, in step S2, the sizing is performed by a single dipping and single rolling sizing method.
[0021] Preferably, in step S3, the warp density is set to 300 pieces (10 cm)-1 , the weft density is set to 300 (10cm) -1 .
[0022] Preferably, the above-mentioned desizing-free sizing process for viscose filament Hada fabric further comprises S4: using an organic silicon type softening finishing agent to soften the fabric obtained in step S3.
[0023] A Hada fabric woven by adopting the above-mentioned viscose filament Hada fabric desizing-free sizing process.
[0024] Compared with the prior art, the desizing-free sizing material and slurry for viscose filament Hada fabric are suitable for weaving viscose filament into Hada fabric by adopting the desizing-free sizing process. The performance of the yarn after sizing with the sizing material, such as strength and wear resistance, is greatly enhanced, so that the desizing-free fabric is superior in mechanical properties and wrinkle resistance compared with the traditional sizing fabric. The fabric is not easy to deform and the fabric style is more suitable for Hada fabric. In addition, the desizing-free sizing process conforms to the characteristics of medium and low temperature sizing, saves energy, reduces the discharge of desizing wastewater, conforms to the development trend of green sizing, and is of great significance to the protection of the ecological environment in Tibet. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Polarized light microscope pictures of slurries prepared with different formulations in Example 1 of the present invention;
[0026] Figure 2 This is a schematic diagram of an electron microscope of the original yarn in Example 2 of the present invention;
[0027] Figure 3 This is a schematic diagram of an electron microscope of sizing yarn obtained by sizing with recipe 2 in Example 2 of the present invention;
[0028] Figure 4 This is a schematic electron microscope diagram of the sizing yarn obtained by conventional sizing treatment in Example 2 of the present invention. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but the following embodiments are by no means intended to limit the present invention in any way.
[0030] Example 1
[0031] A desizing-free sizing material for viscose filament Hada fabric is prepared by compounding oxidized acetate starch and PVA-0588 according to the weight ratio shown in Table 1 below; wherein the oxidized acetate starch adopts a composite modified starch provided by Guangxi Mingyang Agricultural Reclamation Co., Ltd., which is prepared by esterifying and oxidizing the mixed starch with corn starch and cassava starch as raw materials, and the infrared spectrum characterization result is: 3200-3400cm -1 The absorption peak of 1730cm-1 There is an obvious C=O stretching vibration characteristic peak at 1560cm -1 There is a relatively obvious absorption peak; PVA-0588 (volatile matter is 4.1%) is a product provided by Tianjin Xindema Group Co., Ltd.
[0032] Table 1:
[0033]
[0034] The viscose filament Hada fabric desizing-free slurries prepared by the above five formulations are prepared into slurries, and the specific preparation methods are as follows: 1) adding water to the slurry to make the solid content of the slurry 2wt.%; then stirring at 95°C for 30 minutes to completely gelatinize the oxidized acetate starch; and finally keeping warm at 60°C for 30 minutes.
[0035] The degree of starch gelatinization in the slurries prepared with the above five formulations was observed using a WY-630MS polarizing microscope. Figure 1 As shown, (a) to (e) are polarizing microscope images of the slurries prepared from Recipe 1 to Recipe 5, respectively. In the polarizing microscope images of the five slurries, it can be seen that no polarizing cross appears, proving that the starch in the slurry has been completely gelatinized and the PVA has also been dissolved.
[0036] The properties of the slurry prepared above were tested, including the slurry apparent viscosity, slurry transparency and slurry surface tension.
[0037] (1) Slurry apparent viscosity:
[0038] The NDJ-79 rotary viscometer was used to measure the viscosity and viscosity stability of the slurries of the above five formulations. The specific test method was as follows: the prepared slurry was kept at 60°C for 30 minutes and then measured for the first time, and then measured every 1 hour under the heat preservation state, for a total of 6 times. The specific test results are shown in Table 2 below.
[0039] Table 2:
[0040]
[0041]
[0042] The apparent viscosity of the slurries prepared in each formulation in Table 2 is in mPs·S.
[0043] According to the test results in Table 2, the apparent viscosity of the five slurries is ≤2.2mPs·S, and the apparent viscosity fluctuation does not exceed 0.3mPs·S with increasing insulation time, and the stability is good; the reason for this test result is that the oxidized acetate starch has an ester group, and the partially alcoholyzed PVA contains a large number of ester groups. According to the principle of like dissolves like, the two have good miscibility, the slurry viscosity is relatively small, and the fluidity is good; and, as the content of PVA-0588 increases, the viscosity of the slurry gradually decreases, but due to the low solid content, the slurry viscosity between the formulations is slightly different, and the volatility of the slurry is not large.
[0044] (2) Slurry transparency:
[0045] The compatibility of the slurry affects the stability of the slurry during the sizing process, which can be expressed by the transparency of the slurry. The higher the transparency, the better the compatibility of the components in the slurry, which is conducive to maintaining the stability of the sizing quality. Based on this, the compatibility characterized by transparency affects the sizing quality.
[0046] The prepared slurry was cooled to room temperature, and the transmittance of the slurry was measured at 620 nm using a Thermo Evolution 201 UV-visible spectrophotometer, with deionized water as a blank control; the measurement was performed every 1 h, for a total of 6 times; the specific test results are shown in Table 3 below.
[0047] Table 3:
[0048] project Recipe 1 Recipe 2 Recipe 3 Recipe 4 Recipe 5 <![CDATA[Transmittance T0 / %]]> 84.116 86.034 88.942 90.251 92.974 <![CDATA[Transmittance T1 / % after 6 h]]> 83.325 84.910 87.221 88.368 92.132 ΔT 0.791 1.124 1.721 1.883 0.842
[0049] From the test results in Table 3, it can be seen that the transparency of the newly prepared slurries of the five formulas is relatively high. The main reason is that the oxidized acetate starch has a high transparency and good miscibility with PVA-0588 due to the cleavage of the macromolecular chain due to oxidation, and the degree of polymerization and molecular weight of the oxidized acetate starch decrease compared with ordinary starch. In addition, with the addition of PVA-0588, the transparency gradually increases. This is because the partial alcoholysis of PVA-0588 can promote the hydration of PVA-0588, and the enhancement of hydration capacity is conducive to the formation of hydrogen bonds with water molecules, so that the combined slurry The transparency of the slurry is high; however, on the other hand, in the long-term transparency test of the slurry, the smaller the change in the transparency value, the better the anti-coagulation property of the slurry; from the test results in Table 3, the slurries prepared with Formula 1 and Formula 5 have the best transparency, followed by the slurry prepared with Formula 2; the slurries prepared with Formula 3 and Formula 4 have poor transparency, that is, the suitability of the compounding ratio of the above two formulas is poor; when the ratio of PVA-0588 to composite modified starch reaches 1:1, the anti-coagulation property is the worst. It can be seen that the closer the ratio of starch to PVA-0588 is to 1, the worse the stability of the slurry.
[0050] (3) Slurry surface tension
[0051] The surface tension of the slurry affects the permeability. Good permeability is the premise of good adhesion, which affects the bundling of filament yarn and the mechanical properties of yarn, and then affects the weavability. The permeability of the slurry to the fiber is closely related to the surface tension. The smaller the surface tension, the better the slurry penetrates into the yarn and wets the surface, which helps to improve the cohesion between fibers.
[0052] The prepared slurry was cooled to room temperature and its surface tension was tested using a JK99FM automatic surface tension meter. The average value was obtained after three tests. The surface tension test results of slurries with different ratios are shown in Table 4 below.
[0053] Table 4:
[0054] project Surface tension / (mN / m) Recipe 1 51.547 Recipe 2 50.874 Recipe 3 50.272 Recipe 4 49.736 Recipe 5 49.402
[0055] It can be seen from the test results in Table 4 that the surface tension of the slurry formed by single oxidized acetate starch as the slurry (Formula 1) is the largest. This is because the pure starch slurry has high viscosity and flow resistance, resulting in poor penetration of the slurry of Formula 1 into the interior of the yarn and poor wetting effect on the surface. As the compounding and addition ratio of PVA-0588 and oxidized acetate starch increases, the surface tension of the slurry gradually decreases. This is because the partially alcoholyzed PVA-0588 contains hydrophobic acetyl side groups. The more acetyl side groups there are, the more unevenly they are distributed in the molecule, and the lower the surface tension of the corresponding slurry.
[0056] In summary, according to the performance test results of the above five sizing solutions, the sizing solutions of Formula 2 and Formula 5 are better than those of the other three formulations in terms of sizing performance and are more suitable for sizing. However, the final selection of sizing solution also needs to be considered from the two aspects of sizing yarn and woven product effects.
[0057] As comparative example 1, in this specific embodiment, an attempt was also made to compound oxidized acetate starch and PVA-1799 in a weight ratio of 4:1 to form a slurry. However, PVA-1799 has a high degree of polymerization, poor solubility, and high viscosity, and the alcoholysis of PVA-1799 is 99%, resulting in almost no ester group in the almost completely alcoholysed PVA, poor miscibility with oxidized acetate starch, and easy stratification of the slurry. Therefore, it is not suitable for mixing with oxidized acetate starch for the desizing-free process of viscose filament Hada. In addition, the desizing-free process requires a low solid content and low viscosity of the slurry. If the slurry prepared with PVA alone is used for sizing, the sizing effect will inevitably be poor, so it is not suitable for the desizing-free process.
[0058] Example 2
[0059] The viscose filaments were warp-sized by using an ASS3000 fully automatic single yarn sizing machine; the sizing solutions used for sizing were the five sizing solutions prepared in Example 1, and 0.5wt.% of oil was added to the five sizing solutions for lubrication; specifically, the sizing was performed by single dipping and single rolling sizing, the sizing temperature was set to 60°C, the drying room temperature was set to 60°C, the sizing speed was 20m / min, and the pressure of the sizing roller was 0.2MPa, and the sizing samples were obtained. Among them, the untwisted viscose filaments were 13.3tex untwisted viscose filaments provided by Jilin Carbon Valley Carbon Fiber Co., Ltd.; the oil was a mixture of castor oil and castor oil polyoxyethylene ether in a weight ratio of 1:1, the castor oil was purchased from Tianjin Damao Chemical Reagent Factory, and the castor oil polyoxyethylene ether was purchased from Shanghai McLean Biochemical Technology Co., Ltd.
[0060] As Comparative Example 2, the same viscose filaments are simultaneously sized with conventional sizing sizing agents for warp sizing; the sizing agent is a composite of oxidized etherified pea and corn starch and oxidized corn starch in a weight ratio of 4:1, and water is added to form a slurry with a solid content of 5 wt.%; the conventional sizing process is used for sizing, specifically, the sizing temperature is set to 95°C, the sizing speed is set to 20 m / min, and the sizing roller pressure is set to 0.2 MPa.
[0061] The five sized yarn products obtained by the treatment of Example 2 and the sized yarn products obtained by the treatment of Comparative Example 2 were tested, including the surface morphology of the sized yarn and the wear resistance and mechanical properties of the sized yarn. Before the test of the wear resistance and mechanical properties of the sized yarn, the samples to be tested were pre-humidified and humidified, and the test was carried out in a constant temperature and humidity environment (temperature (20±2)°C, humidity (65±4)%).
[0062] (1) Sizing surface morphology:
[0063] A desktop scanning electron microscope (pHenom XL) was used to obtain the surface morphology electron micrographs of the raw yarn and the sizing filament yarn to analyze the changes in their surface morphology.
[0064] like Figure 2 Shown is an electron microscope image of the original yarn; it can be seen from the figure that the original filament yarn has poor cohesion and loose structure, resulting in low strength and poor wear resistance.
[0065] like Figure 3 The figure shows the electron microscope image of the sizing yarn obtained by the sizing treatment with the sizing agent of formula 2. It can be seen from the figure that the bundling property of the sizing yarn is significantly improved compared with the yarn before sizing. This indicates that the sizing agent forms a relatively uniform sizing film on the surface of the yarn, which improves the bundling property of the filament yarn after sizing, and the sizing agent penetrates to form a bonding layer.
[0066] like Figure 4The figure shows the electron microscope image of the sizing yarn obtained by the traditional sizing treatment. It can be seen from the figure that the sizing film coverage rate on the sizing yarn surface is higher, that is, the sizing rate of the sizing yarn is higher, but the bundling of the filament yarn after sizing is not as good as Figure 3 The effect shown.
[0067] In terms of the surface morphology of the sizing yarn, the electron microscope images of the sizing yarns treated with the other four formulations are similar to those of Figure 3 The effects shown are similar, both of which are manifested in that the bundling of the filament yarn after sizing is improved, the sizing material penetrates, and a bonding layer is formed.
[0068] (2) Wear resistance and mechanical properties of sizing yarn:
[0069] The mechanical properties of filament yarn are a direct reflection of the quality of sizing, which affects the smooth progress of the weaving process. Good mechanical properties can reduce ends of yarn breakage, reduce hairiness, improve weaving efficiency, and improve the mechanical properties of fabrics. The viscose filament raw material has poor bundling and poor direct spinnability. It needs to be sized to increase the bundling of the fiber, reduce the fuzzing phenomenon in the subsequent weaving process, and further avoid ends of yarn breakage during weaving, which affects weaving.
[0070] Wear resistance was tested by TM-200iA high-speed yarn friction cohesion tester, and the test conditions were as follows: friction angle 116°, tension load 150g, and combing needle brushing speed 120 times / min; mechanical properties were tested by YG061-1500 electronic single yarn strength tester, and the breaking strength and breaking elongation of filament yarn after sizing were tested; wherein, the gauge length was set to 250mm, and the stretching speed was set to 250mm / min, and the reference standard was GB / T 3916-2013 "Determination of the breaking strength and breaking elongation of single yarn of textile package yarn (CRE method)"; the sizing rate of sizing yarn was calculated by alkali desizing method, and the sizing yarn sample was put into 2% sodium hydroxide solution and boiled for 10 minutes, then taken out, rinsed with clean water, dried and weighed. The specific test results are shown in Table 5 below.
[0071] Table 5:
[0072]
[0073] It can be seen from the test results in Table 4 that, compared with the original yarn, the wear resistance and strength of the yarn after using the five sizing slurries are further improved; among them, the permeability of single oxidized acetate starch as a sizing agent (Formula 1) is poor, and neither esterification nor oxidative denaturation can change the brittle and hard ring structure of the starch macromolecular chain segment, which is easy to form a hard and brittle slurry on the yarn surface, affecting the strength and elongation of the yarn; while the PVA-0588 macromolecular main chain has good flexibility, high regularity, and good film-forming properties; therefore, oxidized acetate starch needs to be used in combination with PVA-0588 to show better sizing advantages.
[0074] According to the test results in Table 4, compared with traditional sized yarn, the sizing rate of desizing-free sized yarn is lower, mainly due to the lower solid content; although the sizing rate of traditional sized yarn is high, which makes its reinforcement rate higher than that of desizing-free sized yarn and has higher strength, the elongation reduction rate of traditional sized yarn is slightly worse, and the higher sizing rate makes the size film on the surface of the sized yarn thicker, resulting in a decrease in elongation at break.
[0075] In the slurry formed by Formulations 2 to 5, as the proportion of PVA-0588 increases, the mechanical properties and wear resistance of the sizing yarn show a trend of first increasing and then decreasing. This is because the carboxyl groups in the oxidized acetate starch weaken the interaction between starch molecules and improve the adhesion to the viscose fiber. The sizing film formed by the esterified starch is more resilient, which makes the mechanical properties of the sizing yarn better and the sizing performance is better. However, there are a large number of ester groups in the partially hydrolyzed PVA, which reduces the number of hydrogen bonds between hydroxyl groups formed with cellulose fibers, reduces the sizing rate, reduces the strength of the bonding layer, and the wear resistance of the yarn becomes worse. In particular, the elongation at break of Formulations 3 to 5 is too low, which does not meet the mechanical condition requirements for sizing yarn.
[0076] The reinforcement rate of traditional sized yarn is higher than that of desizing-free sized yarn, mainly because of its high sizing rate and higher strength, but slightly worse elongation reduction. The higher sizing rate makes the size film on the surface of the sized yarn thicker and the elongation at break is also reduced.
[0077] In summary, from the perspective of sizing effect, the use of sizing agent of Formula 2 has better sizing performance and is more conducive to the subsequent weaving process.
[0078] Example 3
[0079] A DSWa-02 digital sample warping machine was selected as the warping machine, and the five sizing yarns obtained by the treatment in the above embodiment 2 were woven to achieve a warping length of 3m; a sample arrow loom was selected as the loom, and the ground structure design was one-up and three-down weft twill, and the warp and weft densities were set to 300 strands / 10cm; after weaving, the fabric was softened with a silicone softening finishing agent to obtain a viscose filament Hada fabric; wherein the softener used a silicone softening finishing agent, which was specifically purchased from Shanghai Juanrui Chemical Co., Ltd.
[0080] As Comparative Example 3, the weaving conditions are kept the same, and the sized yarn obtained in Comparative Example 2 is woven; unlike the desizing-free fabric in Example 2 which does not require desizing treatment, the conventional sizing process fabric in Comparative Example 3 still needs to be desizing treated, and the specific desizing method is alkali desizing, and the fabric is immersed in a NaOH solution with a concentration of 1 wt.% according to a fabric ratio of 40 mL / g, boiled for 30 min, washed with clean water and then dried; after desizing, the fabric is softened and finished in the same manner.
[0081] The fabrics woven in Example 3 and Comparative Example 3 were subjected to performance tests, including fabric specifications and mechanical properties, fabric wrinkle resistance, fabric bending properties, and fabric style. Before the test, the samples to be tested were pre-humidified and humidified, and the test was conducted in a constant temperature and humidity environment (temperature (20±2)°C, humidity (65±4)%).
[0082] (1) Fabric specifications and mechanical properties test:
[0083] Fabric specifications include thickness and weight. Thickness refers to the standard GB / T 3820-1997, and is tested using a YG141LA digital fabric thickness tester, with a presser foot area of (2000±20) mm, a weight load of 400 cN, and a press time of 10 s. Weight refers to the standard GB / T 4669-2008, and is weighed using a balance, accurate to 0.001. Fabric tensile performance refers to the standard GB / T3923.1-2013, and a YG065 electronic fabric strength tester is used; the gauge length is 200 mm, and the tensile speed is 100 mm / min. The tear strength refers to the standard GB / T3917.2-2009, with a gauge length of 100 mm and a tensile speed of 100 mm / min. The specific test results are shown in Table 6 below.
[0084] Table 6:
[0085]
[0086]
[0087] It can be seen from the test results of Table 6 that the gram weight and thickness of the fabrics with the traditional sizing process are relatively small, mainly because the alkali desizing of the fabric causes the weft yarn to shrink to a certain extent, and the yarns are arranged more closely, resulting in an increase in gram weight and thickness; while the desizing-free fabric woven in Example 3, due to the use of the light sizing process, the lower sizing rate makes the gram weight and thickness of the fabric less affected, making the Hada fabric have a lighter feel; and, since the mechanical properties of the sizing yarn are higher than those of the original yarn, the mechanical properties of the desizing-free fabric are better than those of the traditional desizing fabric, and the desizing-free process avoids the decrease in the mechanical properties of the yarn fabric caused by desizing, thereby improving the mechanical properties of the Hada fabric. According to the mechanical property test comparison of the above three groups of desizing-free fabrics, the desizing-free fabric woven by Formula 2 has the best mechanical properties, followed by Formula 1, and Formula 3 is the worst, mainly because the performance of the sizing yarn in Formula 3 affects the performance of its fabric, resulting in Formula 3 being unsuitable for the desizing-free warp sizing of Hada.
[0088] (2) Fabric wrinkle resistance:
[0089] Hada fabrics will have creases during storage and use, and these creases directly affect their appearance. Based on this, the anti-wrinkle performance of fabrics is tested with reference to the standard: GB / T 3819-1997, using the YG541L digital fabric wrinkle elasticity tester, and the vertical method is selected. The specific test results are shown in Table 7 below.
[0090] Table 7:
[0091]
[0092] From the test results in Table 7, it can be seen that the recovery angle of the desizing-free fabric is larger, indicating that its wrinkle resistance is better than that of the traditional sizing fabric. This is mainly because the warp yarn surface of the desizing-free fabric is covered by the size film, the friction resistance between fibers is small, and the low resistance sliding is conducive to the recovery of the fiber after deformation. The smoother the yarn surface, the better the wrinkle resistance, and the greater the stiffness of the warp yarn, the less likely the fabric is to deform, and the crease recovery is good. After desizing, the friction resistance between fibers of the traditional sizing process fabric increases, the recovery is poor, and the wrinkle resistance is poor. According to the comparison of the wrinkle resistance test of the above three groups of desizing-free fabrics, the wrinkle resistance of the desizing-free fabric of formula 1 is poor, and formula 3 is the best, mainly because the main chain of PVA is a carbon-carbon chain, which is a flexible chain; similarly, formula 2 is also within the appropriate selectable range; and the ring structure of the main chain of the starch macromolecule is a rigid structure, which makes the wrinkle resistance of the fabric of formula 1 worse.
[0093] (3) Fabric bending performance:
[0094] Bending stiffness refers to the ability of fabric to resist bending deformation. The larger the value, the stiffer the fabric. Based on this, the bending performance of fabrics refers to the standard: GB / T 18318.1-2009, using the LLY-01 fabric stiffness tester, and the inclined plane method. The specific test results are shown in Table 8 below.
[0095] Table 8:
[0096]
[0097] It can be seen from the test results of Table 8 that the desizing-free fabric has greater bending stiffness, better rigidity and slightly worse softness. Since the fabric has not been desizing treated, there is a size film on the surface of the warp yarn, which will increase the stiffness of the yarn and thus affect the stiffness of the fabric. However, the difference between the two is small, mainly because light sizing is used, the sizing rate is low, and the slurry has good film-forming properties and strong toughness of the size film, which has little effect on the bending performance of the fabric; and the desizing-free fabric has appropriate softness and is more suitable for Hada fabric. According to the comparison of the bending performance tests of the above three groups of desizing-free fabrics, the desizing-free fabric of Formula 1 is stiffer, mainly due to the rigid ring structure of the main chain of the starch macromolecule, which makes the bending performance of the fabric of Formula 1 worse; and the desizing-free fabrics of Formulas 2 and 3 are relatively soft, so the two formulas are more suitable for the desizing-free yarn weaving process of this application.
[0098] (4) Fabric style:
[0099] Fabric style is a person's sensory experience of the physical properties of fabrics. There are more subjective factors in the evaluation of fabric style. The KES-FB fabric style meter can reflect the deformation process of fabrics under the action of small external forces and make a more comprehensive and objective evaluation of fabric style. Based on this, the KES-FB fabric style meter was used to test the fabric styles of two fabrics. The sampling size was 20cm×20cm. The fabrics were ironed flat before the test to avoid affecting the test results. The specific test results are shown in Table 9 below.
[0100] Table 9:
[0101]
[0102] The smaller the values of the average friction coefficient and surface roughness, the smoother the fabric surface; the larger the compression ratio work value, the fluffier the fabric; the smaller the shear stiffness value, the less likely it is to undergo shear deformation; the larger the tensile linearity, the less likely it is to undergo tensile deformation. It can be seen from the test results in Table 9 that the surface of the desizing-free fabric is smoother, the fabrics are tighter, and the ability to resist deformation is better. This is because after the desizing treatment, the size film on the surface of the warp yarn is removed, the yarn surface becomes rough, and then affects the surface properties of the fabric; the traditional sizing process fabric is more fluffy and the fabric is easy to deform, so the style of the desizing-free fabric is more suitable for Hada fabric. According to the fabric style test comparison of the above three groups of desizing-free fabrics, the surface performance and fluffiness are slightly different, the fabric of formula 1 is not easy to deform, but the feel is stiffer, which is not suitable for the fabric style of Hada; therefore, the desizing-free fabrics of formulas 2 and 3 feel soft in fabric style and are not easy to deform, so the two formulas are more suitable for the desizing-free yarn weaving process of this application.
[0103] In summary, based on the above-mentioned multiple performance tests on the slurry performance, sizing yarn performance, and fabric performance obtained by the desizing-free sizing yarn weaving process of the five formulas, and the analysis of the test results, Formula 2 is a slurry formula that matches the desizing-free sizing yarn weaving process of the present application. By using this slurry to match the desizing-free sizing yarn weaving process, the most expected Hada fabric can be woven.
[0104] Example 4
[0105] According to the exploration of various properties of different formulations of slurries in Examples 1 to 3 above, the slurry of Formula 2 has the best weaving effect for viscose filament weaving Hada fabrics, so the specific weaving process parameters for its use in Hada fabric weaving are further explored.
[0106] The raw material is viscose filament after sizing, and the sizing liquid prepared by formula 2 is used. The warping machine is DSWa-02 digital sample warping machine, and the warping length is 3m. The loom is a sample arrow loom. The ground structure is a one-up and three-down weft twill. The warp density is designed to be 300 strands / 10cm and 420 strands / 10cm. Each warp density corresponds to a different weft density. A total of 6 fabrics are designed. The fabric specifications are shown in Table 10.
[0107] Table 10:
[0108] Sample <![CDATA[Ends per 10 cm -1 )]]> <![CDATA[Weft density / (ends per (10 cm) -1 )]]> 1# 300 200 2# 300 250 3# 300 300 4# 420 180 5# 420 240 6# 420 300
[0109] The surface friction performance of six kinds of fabrics, that is, the roughness or fineness of the fabric surface contact feeling, was tested; specifically, the test used KES-FB4 friction and surface roughness tester to test the fabrics, and obtained three indicators: average friction coefficient MIU, mean friction coefficient difference MMD and surface roughness SMD; the specific test results are shown in Table 11.
[0110] Table 11:
[0111] Sample Average friction coefficient MIU Friction coefficient mean difference MMD Surface roughness SMD / μm 1# 0.1192 0.0118 3.9753 2# 0.0983 0.0078 3.6237 3# 0.0822 0.0063 2.4673 4# 0.1200 0.0106 4.6913 5# 0.1102 0.0095 3.6797 6# 0.0927 0.0072 1.6975
[0112] From the test results in Table 11, it can be seen that the average friction coefficient MIU and the average difference in friction coefficient MMD of 3# fabric are the smallest because its warp and weft densities are the same, so its surface is the flattest because its warp and weft densities are the same; 6# fabric has the largest warp and weft density and the most interlacing points, so its surface roughness SMD value is the smallest and the fabric feels smooth; it can be seen that the tighter the fabric, the smoother its surface and the better the flatness; according to the test results, 3# fabric is most suitable for weaving Hada fabric.
[0113] The compression performance of six kinds of fabrics, that is, the compression deformation performance produced when the fabrics are compressed by a certain positive pressure, was tested to obtain the fluffiness, fullness, etc. of the fabrics; specifically, the test used the KES-FB3 compression performance instrument to obtain the three index results of the fabric compression linearity LC, compression ratio work WC and compression recovery rate RC; the specific test results are shown in Table 12.
[0114] Table 12:
[0115]
[0116] The compression linearity LC indicates the softness of the fabric. The larger the value, the softer the fabric. The compression work WC indicates the fluffiness of the fabric. The larger the WC value, the fluffier the fabric. The compression recovery rate RC indicates the fullness of the fabric. The larger the value, the better the compression recovery of the fabric. From the test results in Table 12, it can be seen that the compression linearity LC and compression work WC of the 4# fabric are both the largest, and the fabric feels the fluffiest and softest; the warp and weft density of the 6# fabric is the highest, and the fabric is the stiffest; the compression recovery rate RC of the 3# fabric is the largest, indicating that the fabric has the best compression recovery; it can be seen that the lower the warp and weft density of the fabric, the greater the difference, the fluffier, and the fuller the feel.
[0117] The bending properties of six kinds of fabrics, that is, the softness of the fabrics, were tested. The bending properties of fabrics are very important properties. They should be moderate, not too stiff to affect the hand feel, and not too soft. This test uses the KES-FB2 bending properties tester to test the two indicators of the fabric bending stiffness B and bending hysteresis moment 2HB; the specific test results are shown in Table 13.
[0118] Table 13:
[0119]
[0120] From the test results in Table 13, it can be seen that the bending stiffness B represents the stiffness of the fabric. Accordingly, the value of the bending stiffness B of the 6# fabric is the largest, indicating that the fabric is the most difficult to bend and has the hardest feel, while the 1# fabric has the softest feel. The bending hysteresis moment 2HB represents the recovery performance of the fabric during the bending deformation process. The smaller the value, the better the recovery performance. Accordingly, the bending hysteresis moment 2HB of the 6# fabric is the smallest, indicating that the 6# fabric has the best recovery performance, because its warp and weft density are both high, so the fabric has better recovery performance; the other fabrics are not much different; the greater the warp and weft density, the greater the bending stiffness B value, but the smaller the bending hysteresis moment 2HB, indicating that the more interlacing points the fabric has, the harder the fabric feels; Hada fabric requires a soft feel, and the 1# fabric is the softest, but the density between the yarns is too small and easy to slip; the 6# fabric feels too hard and is not very suitable. To meet the needs of Hada's daily activities, the softness should be moderate.
[0121] The shear performance of six kinds of fabrics was tested. The most important indicator of the shear performance of fabrics is the shear stiffness G, which represents the ability of the fabric to resist shear deformation. When the fabric is subjected to a pair of opposite forces or moments in its own plane, the warp and weft angles change, causing the fabric to shear. This test uses the KES-FB1 tensile-shear tester to test the shear stiffness G, shear hysteresis moment 2HG and other indicators to characterize the anti-shear performance of the fabric; the specific test results are shown in Table 14.
[0122] Table 14:
[0123]
[0124] From the test results in Table 14, it can be seen that the shear stiffness G of fabric 3# is the smallest, indicating that it has the best ability to resist shear deformation, and fabric 1# is the worst, indicating that it is most easily deformed. Fabric 6# has the smallest shear hysteresis moment and the best deformation recovery ability, and fabric 1# has the largest, indicating that its formability is poor. The higher the warp and weft density, the better the fabric's ability to resist shear deformation, but the worse its recovery ability. The fabric has a high warp and weft density, the yarns are close together, and the movable space is small, so it is not easy to deform, and once deformed, it is not easy to recover.
[0125] The tensile properties of the six fabrics are as follows: The tensile properties of the fabric refer to the degree of deformation and elongation produced when the fabric is stretched in a certain direction by an external force, which can reflect the elasticity and firmness of the fabric. The tensile properties of the fabric are characterized by indicators such as tensile linearity LT, tensile specific work WT and tensile recovery rate RT. The specific test results are shown in Table 15.
[0126] Table 15:
[0127]
[0128] The larger the value of the tensile linearity LT, the smaller the value of the tensile recovery rate RT, indicating that the fabric is less likely to be stretched and deformed, but the elasticity is poor. From the test results in Table 15, it can be seen that the value of the tensile linearity LT of fabric 3# is the largest, and the fabric is least likely to be stretched and deformed. The tensile linearity LT value of fabric 4# is the smallest, and the fabric is most likely to be deformed, but the tensile recovery rate RT is the largest and the elasticity is the best; the tensile work WT represents the ability of the fabric to resist tensile deformation. The larger the value, the greater the fabric strength, but the relatively poor hand feel; the tensile work WT of fabric 6# is the largest, and the fabric strength is the highest. The tensile work WT of fabric 4# is the smallest, and the strength is the worst, but the hand feel is soft. It can be seen that the higher the warp and weft density of the fabric, the smaller the space for the yarn to move, and the less likely the fabric is to be stretched and deformed; fabrics 3# and 6# with higher warp and weft density are less likely to be stretched and sheared.
[0129] In summary, from the above comprehensive performance and application scenarios of Hada, the 3# fabric in Example 4 is the best, that is, in terms of the specific weaving parameter selection, the warp density is appropriately set to 300 roots (10 cm) -1 ~420 pieces (10cm) -1 , more preferably 300 roots﹒ (10cm) -1 The weft density is preferably set to 200 (10cm) -1 ~300 pieces (10cm) -1 , more preferably 300 roots﹒ (10cm) -1 .
Claims
1. A desizing-free slurry for viscose filament Hada fabric, characterized in that: It is compounded by oxidized acetate starch and PVA-0588, and the weight ratio of the two is (15-17):
4.
2. The desizing-free slurry for viscose filament Hada fabric according to claim 1, characterized in that: Oxidized acetate starch is prepared from corn starch and cassava starch through esterification and oxidation double modification.
3. A slurry prepared by using the desizing-free slurry of the viscose filament Hada fabric according to claim 1, characterized in that: Add water to the slurry to make the solid content of the slurry 2wt.% to 5wt.%; then place it at 95℃ to 100℃ and stir it for 30min to 40min; finally place it at 60℃ to 65℃ and keep it warm for 30min to 40min.
4. A desizing-free sizing weaving process for viscose filament Hada fabric using the slurry as claimed in claim 3, characterized in that: The steps are: S1, preparing a slurry, and adding 0.5wt.% of an oil agent into the slurry; S2. Sizing the viscose filaments: the sizing temperature is set to 55°C to 60°C, the drying room temperature is set to 55°C to 60°C, the sizing speed is 20m / min to 25m / min, and the pressure of the sizing roller is 0.2MPa to 0.3MPa to obtain sizing yarn; S3, weaving the sizing yarn into Hada fabric: the warp density is set to 300 (10cm) -1 ~420 pieces (10cm) -1 , the weft density is set to 200 (10cm) -1 ~300 pieces (10cm) -1 .
5. The desizing-free sizing process for viscose filament Hada fabric according to claim 4, characterized in that: In step S1, the oil agent is a mixture of castor oil and castor oil polyoxyethylene ether in a weight ratio of 1:
1.
6. The desizing-free sizing process for viscose filament Hada fabric according to claim 4, characterized in that: In step S2, the viscose filaments are 11 tex to 15 tex viscose filaments.
7. The desizing-free sizing process for viscose filament Hada fabric according to claim 4, characterized in that: In step S2, the sizing is performed by a single dipping and single rolling sizing method.
8. The desizing-free sizing process for viscose filament Hada fabric according to claim 4, characterized in that: In step S3, the warp density is set to 300 pieces (10 cm) -1 , the weft density is set to 300 (10cm) -1 .
9. The desizing-free sizing process for viscose filament Hada fabric according to claim 4, characterized in that: The method further comprises S4, using an organic silicon type softening finishing agent to perform softening finishing on the fabric obtained in step S3.
10. A Hada fabric woven by the desizing-free sizing process of the viscose filament Hada fabric according to any one of claims 4 to 9.
Citation Information
Patent Citations
Blended yarn sizing slurry mixing
CN101187168A
Sizing method suitable for weaving at low-humidity environment
CN105586738A
PVA-free, green and environment-friendly size and sizing process thereof
CN109763331A
Wet sizing hairiness attaching device and method after sizing
CN116289029A